A Phonological Description of the Local Dialect of Žetinci - Sicheldorf (SLA Data Point T414) - Kumin Horvat, Mojca (Jezikoslovni zapiski, 2023)
This article presents the local dialect of Žetinci (Germ. Sicheldorf; SLA T414), which belongs to the Prekmurje dialect of the Pannonian dialect group. It describes its basic phonetic and accentological characteristics. A phonological description of the local dialect is presented using dialect material collected by Zinka Zorko for Slovenian Linguistic Atlas (SLA) in 1988.